2014
DOI: 10.5811/westjem.2014.2.19158
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Evaluative Components on the Standard Letter of Recommendation (SLOR) in Emergency Medicine

Abstract: IntroductionThe standard letter of recommendation in emergency medicine (SLOR) was developed to standardize the evaluation of applicants, improve inter-rater reliability, and discourage grade inflation. The primary objective of this study was to describe the distribution of categorical variables on the SLOR in order to characterize scoring tendencies of writers.MethodsWe performed a retrospective review of all SLORs written on behalf of applicants to the three Emergency Medicine residency programs in the Unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 8 publications
5
35
0
Order By: Relevance
“…A small percentage of OTO LORs were written by community OTOs (4.2%, n 5 35). Of the remaining 123 letters written by non-OTOs, 36.6% (n 5 45) were composed by general surgeons, 24.4% (n 5 30) by surgeons in other subspecialties, 13.0% (n 5 16) by internists, 16.3% (n 5 20) by other nonsurgical physicians, 7.3% (n 5 9) by researchers (with Ph.D. degrees), and 2.4% (n 5 3) by writers whose position was not specified. Letter writers were located throughout the United States, including Puerto Rico.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A small percentage of OTO LORs were written by community OTOs (4.2%, n 5 35). Of the remaining 123 letters written by non-OTOs, 36.6% (n 5 45) were composed by general surgeons, 24.4% (n 5 30) by surgeons in other subspecialties, 13.0% (n 5 16) by internists, 16.3% (n 5 20) by other nonsurgical physicians, 7.3% (n 5 9) by researchers (with Ph.D. degrees), and 2.4% (n 5 3) by writers whose position was not specified. Letter writers were located throughout the United States, including Puerto Rico.…”
Section: Resultsmentioning
confidence: 99%
“…The SLOR has also been purported to reduce the grandiosity often seen in narrative letters; nevertheless, subjective and objective analyses have indicated that letter writers continue to consistently select the highest ranks when reviewing student performance. The SLOR thus fails to achieve one of its goals and yields a seemingly homogenous pool of applicants . Multiple studies have shown that when choosing responses in a Likert‐type scale, as is utilized in the SLOR (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Test scores and memberships in an honorary society should not be taken as evidence of an entirely unchanging applicant pool. However, in light of previously reported difficulties that EM faculty members have in accurately assessing applicants for letters of evaluation and in predicting position on rank lists, it is important that the relative meaning of these scores and designations be understood 14, 15…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Concerns regarding the LOR as an accurate assessment of applicants were raised as long as 35 years ago, 8 with studies showing grade inflation in LORs. [9][10][11] One study reported that less than 2% of candidates were rated using the lowest categories, 9 while another demonstrated that 40% of candidates were rated in the top 10% on a global assessment. 10 When faculty members write LORs, they walk the fine line between writing an honest letter supporting the applicant and diminishing the credibility of these letters by overselling an average candidate.…”
Section: Introductionmentioning
confidence: 99%